2020
DOI: 10.7759/cureus.9853
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Parkinson's Disease: Shared Pathophysiological Links and Possible Therapeutic Implications

Abstract: Diabetes mellitus (DM) is the most common chronic metabolic disease. Parkinson's disease (PD) is considered one of the most common neurodegenerative diseases. There are many similarities between both conditions. Both disorders are chronic diseases. Both diseases result from a decrease in a specific substance: dopamine in PD, and insulin in DM. Besides, both disorders arise due to the destruction of particular cells, dopaminergic cells in PD, and pancreatic beta-cell in DM. Recently, many epidemiological and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 41 publications
2
72
0
Order By: Relevance
“…In addition, previous data based on systemic glucose injections in rats also show an inhibitory effect on the firing of SN DA neurons [ 6 ]. Type II diabetes characterized by increased blood glucose and insulin resistance seems to increase the risk to develop Parkinson’s disease (PD), an age-related neurodegenerative disease in which SN DA neurons are progressively lost [ 7 , 8 ]. Several studies indicate a ciliary role in the function of the dopamine system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous data based on systemic glucose injections in rats also show an inhibitory effect on the firing of SN DA neurons [ 6 ]. Type II diabetes characterized by increased blood glucose and insulin resistance seems to increase the risk to develop Parkinson’s disease (PD), an age-related neurodegenerative disease in which SN DA neurons are progressively lost [ 7 , 8 ]. Several studies indicate a ciliary role in the function of the dopamine system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to discussing the link of PD and DM through their common miRNA biomarkers, many studies revealed common underlying mechanisms in the pathophysiology of both diseases including hyperglycemia, mitochondrial dysfunction, oxidative stress, and inflammation [ 186 ]. PD results mainly from the death of dopaminergic neurons in the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress results from an imbalance between harmful reactive oxygen species (ROS) and the antioxidant process that can lead to dopaminergic cell damage in PD as well as pancreatic β cell damage in DM. miRNAs can regulate ROS and prevent ROS-mediated damage to dopaminergic neurons [ 186 ]. Studies have focused on how to reduce the damage induced by oxidative stress in both PD and DM.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence suggests a link between PD and T2D [ 35 , 36 , 37 , 38 , 39 , 302 ]. T2D is a negative prognostic factor associated with faster motor progression and cognitive decline in PD.…”
Section: The α -Synuclein Link Between Parkinsomentioning
confidence: 99%
“…The data for PD and Alzheimer’s disease (AD) suggest that a number of insults occurring early in life may lead or contribute to both diseases [ 34 ]. Furthermore, strong epidemiological evidence suggests a link between PD and diabetes mellitus type 2 (T2D) [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%